ANALISIS PENGARUH KESADARAN PAJAK, SANKSI DENDA DAN SIKAP FISKUS TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MAKASSAR SELATAN - Saeful Saeful; Abdul Muttalib; Asri Jaya (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
The type of research used in this study is explanation research with a quantitative approach. Samples were obtained by random sampling. Data collection techniques use questionnaire, data types are primary data and secondary data. The primary data was then analyzed using multiple linear regression analysis as an analytical tool using the SPSS 24.0 application.Â  The results of this study are tax awareness has a significant effect on taxpayer compliance, while fines sanctions do not have a positive effect on taxpayer compliance, and the tax authorities' attitude has a positive effect on taxpayer compliance. Where Adjusted R Square of 0.256 shows that 25.6% of tax awareness, fines and attitudes of tax authorities to taxpayer compliance while 74.4% are explained in other factors not examined in this study.